2009
DOI: 10.1093/carcin/bgp319
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile in a glioma cell line resistant to cell death induced by a the chimeric tumor suppressor-1 (CTS-1), a dominant-positive variant of p53—the role of NFκB

Abstract: The identification of genes involved in carcinogenesis and tumor progression is of great interest since these genes might be feasible as candidates for new tumor-targeted therapy strategies. Chimeric tumor suppressor-1 (CTS-1), an artificial synthetic variant of p53, resists common p53 inactivation and could therefore be defined as a dominant-positive p53 variant. Overexpression of CTS-1 induces caspase-independent cell death. We used whole-genome microarray expression analysis in a parental (229(P)) and a CTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…1a) [30], the fact that CPE mRNA expression was significantly reduced in glioblastomas as compared to normal brain tissue in the TCGA and REMBRANDT databases (Fig. 1b), the function of CPE as a peptidase [7] and the knowledge from the literature that low CPE expression is correlated with tumor malignancy in neuroendocrine tumors [11,12,22] prompted us to analyze whether CPE is involved in glioma malignancy and progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1a) [30], the fact that CPE mRNA expression was significantly reduced in glioblastomas as compared to normal brain tissue in the TCGA and REMBRANDT databases (Fig. 1b), the function of CPE as a peptidase [7] and the knowledge from the literature that low CPE expression is correlated with tumor malignancy in neuroendocrine tumors [11,12,22] prompted us to analyze whether CPE is involved in glioma malignancy and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Using whole genome microarray expression analysis, we found CPE to be the most differentially regulated gene in LNT-229 Res cells compared to the parental cell line LNT-229 P [30]. Expression of CPE mRNA was 45-fold lower in LNT-229 Res than in LNT-229 P cells (Fig.…”
Section: Cpe Expression Is Reduced In Gliomas and Associated With Shomentioning
confidence: 90%
See 1 more Smart Citation
“…In this respect, BEX2 expression protects breast cancer cells against mitochondrial apoptosis and is necessary for the normal transition of these cells through G1 cell cycle [2]. In addition, it has recently been shown that down-regulation of BEX1 and BEX2 sensitize LNT-229 glioma cells to the chimeric tumor suppressor-1 (CST-1), a dominant-positive variant of p53, and up-regulation of BEX1 protects these cells to CST-1-induced cell death [22]. These findings further support a pro-survival function for BEX1 and BEX2 using a glioma model.…”
Section: Discussionmentioning
confidence: 99%
“…cDNA from RNA of 229P and 229R cells, that underwent microarray expression analysis, was examined (Figure 2, [20] and data not shown).…”
Section: Resultsmentioning
confidence: 99%